Surface engineering of stainless steel - Pramanik, Alokesh; Hakami, Ferial; Basak, A.; Islam, Mohammad Nazrul; Anandakrishnan, V. (Nova Science Publishers, 2015)
Chromizing and plasma nitriding on steels have attracted interest from industrial sectors because of its attractive properties and ability to apply on different types of steels. This chapter investigates duplex treatment on different types of steels at different treatment conditions. The improvements of the treated surfaces in terms of morphology and thickness, composition, surface hardness and roughness, as well as wear and friction of the engineered layer on different ferrous alloys have been analysed. It was found that several layers of different thickness are formed due to duplex treatment which depends on the carbon content of specimen and temperature of the treatment. Mainly carbides and nitrides of chromium and iron are formed which is controlled by duplex treatment process parameters. These compounds enhance the hardness and wear resistance of the treated surface. The CrxN phase is the main contributor towards high microhardness of duplex treated layers. In addition to high hardness, it also provides excellent wear resistance properties. The plasma nitriding process reduces the coefficient of friction of chromized steels due to the lower friction coefficient of chromium nitride. However, the surface roughness of the treated surface increases due to the intrinsic properties of formed phases.